Wind-Forced Delayed Action Oscillator in Tropical Oceans with Satellite Multi-Sensor Observations - Jiayi Pan; Adam T. Devlin; Hui Lin (Remote Sensing, 2020)
This study investigates correlations among interannual variabilities of sea surface wind, sea surface temperature (SST), and sea surface height anomaly (SSHA) in the tropical region from latitude 15°S to 15°N. Sea surface winds were derived from the European Space Agency (ESA)’s European Remote-Sensing Satellite (ERS)-1/2 scatterometer and the National Aeronautics and Space Administration (NASA)’s QuickSCAT observations; SST data were obtained from the National Oceanic and Atmospheric Administration (NOAA)’s Advanced Very-High-Resolution Radiometer (AVHRR) missions; and the SSHA data were acquired from the NASA TOPEX/Poseidon and Jason-1 altimeter measurements. All these datasets were resampled into 1° × 1° grids between 15°S and 15°N. The annual cycles were removed from all datasets and an empirical orthogonal function (EOF) analysis was applied to extract the major modes of spatial and temporal variability. The first EOF modes of the wind, SST, and SSHA revealed the interannual variability of each data source, reflecting spatio-temporal signatures related to El Nino Southern Oscillation (ENSO) events. The correlation results suggested that, during the strong El Nino period of 1997−1998, the wind variability led the variability of SST. A wind-forced delayed action oscillator (WDAO) system was proposed and analyzed using the ENSO modes of wind and SST data, covering the period from October 1995 to June 2002. The results show that the delayed SST mechanism is the strongest forcing factor in the WDAO system, and the wind forcing is the second strongest forcing factor. The correlations among SST change rate, the wind, and delayed/un-delayed SST also confirm the WDAO analysis’ results.